Literasi Manajemen Mental dan Spiritual Untuk Membangun Kualitas Diri - Arifin, Zainul; Sa’adah, Lailatus; Erawati, Sherly Hesti; Sugiono, Djoko (Jurnal ABM Mengabdi, 2025)
This community service activity aims to provide knowledge and understanding to the community about Literacy of mental and spiritual management, namely; The ability to manage and develop one's mental and spiritual health which involves understanding oneself, managing emotions, and developing strategies to improve mental and spiritual well-being. Mental and spiritual management literacy can help improve the quality of life and build better relationships with oneself, others, and the environment. Service activities are carried out through socialization, counseling, mentoring, and real actions. The participation of Lazis Sabilillah's fostered women is very good and actively contributes to providing advice and direction related to the implementation of activities. The impact of this mentoring activity is expected to help partners in balancing emotions, developing themselves, establishing better relationships, and achieving inner peace. The purpose of this service is to; Improving mental health, productivity, social relationships, quality of life and the achievement of personal goals of Laziz Sabilillah's assisted mothers